The effect of capital structure, institutional ownership, managerial ownership, and profitability on company value in manufacturing companies - Jhonatan Trafalgar; Laely Aghe Africa (The Indonesian Accounting Review, 2019)
This study aimed to examine the effect of capital structure, institutional ownership, managerial ownership, and profitability on company value. It used independent variables such as capital structure with a proxy of Debt to Equity Ratio (DER), institutional ownership, managerial ownership, and profitability with a proxy of Return on Equity (ROE), and the dependent variable such as company value. This study uses secondary data obtained from the Indonesia Stock Exchange (IDX) for the period 2014-2017, with the population of all manufacturing companies listed on the Indonesia Stock Exchange (IDX) with the sample of manufacturing companies in the sector of various industries in the period 2014-2017. It was taken by using purposive sampling method, where they were selected based on the criteria. The data were analyzed using a multiple linear regression analysis with SPSS 23. The results indicated that the Debt to Equity Ratio (DER), institutional ownership, and managerial ownership have no significant effect on company value, while Return on Equity (ROE) has a significant effect on company value. The company's goal can be achieved if the company's performance is able to optimize the value of the company.